Helicobacter Pylori Infection in Canada's Arctic: Searching for the Solutions. (2008) - Cheung, Justin; Goodman, Karen; Munday, Rachel; Heavner, Karen; Huntington, Janis; Morse, John; van Zanten, Sander Veldhuyzen; Fedorak, Richard N; Corriveau, Andre; Bailey, Robert J; for the CANHelp working group,
Abstract : The Canadian North Helicobacter pylori (CAN Help ) working group is a team composed of investigators, health officials and community leaders from Alberta and the Northwest Territories. The group's initial goals are to investigate the impact of H pylori infection on Canada's Arctic communities; subsequent goals include identifying treatment strategies that are effective in this region and developing recommendations for health policy aimed at management of H pylori infection. The team's investigations have begun with the Aklavik H pylori Project in the Aboriginal community of Aklavik, Northwest Territories.